STUDI KEMAMPUAN PATI BIJI ALPUKAT (Persea americana Mill) PREGELATINASI SEBAGAI BAHAN PENGHANCUR PADA TABLET PARACETAMOL KEMPA LANGSUNG - Surya Ningsi; Dwi Wahyuni Leboe; Qurratul Aeni (Jurnal Farmasi UIN Alauddin Makassar, 2016)
Researched about the study of the ability of pregelatinized avocado seeds (Persea americana Mill) starch as disintegrant by direct compression of paracetamol tablets formulation.This Research suppose to know about the ability of pregelatinized avocado seeds starch as disintegrant and optimum concentration of pregelatinized avocado seeds starch as disintegrant on direct compression fulfill the qualification good tablets.Pregelatinized starch produced by heating in its gelatinated temperature, next dried and standardized its measure. Then, evaluated according to granul evaluation. Mixing the mass of tablets, Three formulas were made by disintegrants concentration different (pregelatinized avocado seeds starch) FI 5%, FII 10% dan FIII 15%. Next, evaluated. Tablets compressed by direct compression method and evaluated.The evaluation results pregelatinized avocado seeds starch regularly have particle size 231,3μm, angel of repose 22,76o, fluidity 7,40/det, density true 1,21g/ml, density bulk 0,68 g/ml, density tapped 0,72 g/ml, porosity 40,84 %, compressibility index 3,77%, hausner’s ratio 1,03 and LOD 0,39%. The result show that pregelatinized avocado seeds starch have a good compressibility and fluidity. Result test for tablets show all formulas fulfill the qualification the tablets size uniformity, FII dan FIII fulfill the qualification at the weights uniformity, its hardness regulary 4,51 kg; 6,39 kg; 4,23 kg, friability 1,4%; 0,07%, and 1,50% and disintegration time 0,27 minute; 0,44 minute and 0,04 minute.From this result can be concluded that the pregelatinized avocado seeds starch can be used as a disintegrant on direct compression and the optimum concentration on direct compression pregelatinized avocado seeds of the produce tablets fulfill the qualification a good tablets is FII (10%).